Pengaruh Lokasi dan Fasilitas terhadap Keputusan Pembelian pada Cafe Bang Faizs - Indah Sari; Rahmat Hidayat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
This study aims to determine the effect of location and facilities on purchasing decisions at Bang Faizs Cafe. This research was conducted on Cafe Bang Faizs consumers who are located at Jalan Tengku Fahruddin, Lubuk Pakam I-II Village, Lubuk Pakam District, Deli Serdang Regency in 2020. The population of this study was Café Bang Faizs consumers for 2017 to 2019, amounting to 33,056 people. The research sample consisted of 100 people who were obtained using the Slovin formula with an error rate of 10%. The variables observed in this study consisted of location, facilities and purchase decisions. Location variable indicators consist of access, visibility, parking space, expansion, and the surrounding environment. The facility variable indicators consist of facility design, function value, aesthetics, and conditions. and supporting equipment. Meanwhile, the indicator of purchasing decision variables consists of problem recognition, information search, evaluation of alternatives, and purchasing decisions. Data were collected by distributing questionnaires and literature study, questionnaires were developed from the indicators of each variable that became observations. The data test was conducted with validity and reliability, while the data analysis used multiple linear regression, with hypothesis testing using the coefficient of determination, simultaneous test and partial test. The data were processed using the SPSS program. The results of this study indicate that the location and facilities have a positive and significant effect on purchasing decisions at Bang Faizs Cafe